Youth Suicide Prevention Programming among the Mississippi Band of Choctaw Indians: Effects of the Lifelines Student Curriculum - John P. Bartkowski; Katherine Klee; Xiaohe Xu (MDPI AG, 2024)
Suicide continues to be a leading cause of mortality for young people. Given persistent intersecting forms of disadvantage, Native American adolescents are especially vulnerable to mental health adversities and other suicide risk factors. The Mississippi Band of Choctaw Indians (MBCI) implemented the Choctaw Youth Resilience Initiative (CYRI), a five-year SAMHSA-funded project that began in 2019. This study uses Choctaw student pre-test/post-test survey data to examine the effectiveness of the Hazelden Lifelines Suicide Prevention Training curriculum for youth. A lagged post-test design was used, whereby post-surveys were administered at least one month after program completion. Several intriguing results were observed. First, the lagged post-test model was subject to some pre-to-post attrition, although such attrition was comparable to a standard pre/post design. Second, analyses of completed surveys using means indicated various beneficial effects associated with the Lifelines curriculum implementation. The greatest benefit of the program was a significant change in student perceptions concerning school readiness in response to a suicidal event. Some opportunities for program improvement were also observed. Our study sheds new light on suicide prevention training programs that can be adapted according to Native American youth culture. Program implementation and evaluation implications are discussed in light of these findings.